2021
DOI: 10.3390/ijms221910660
|View full text |Cite
|
Sign up to set email alerts
|

Quinacrine Ameliorates Cisplatin-Induced Renal Toxicity via Modulation of Sirtuin-1 Pathway

Abstract: Renal toxicity is a serious side effect that hinders the use of cisplatin, a commonly used and effective chemotherapeutic agent. Meanwhile, quinacrine is an FDA approved drug that has been stated for its anti-inflammatory effect. Thus, we investigated the ameliorative effect of quinacrine against cisplatin-induced renal toxicity. Single intraperitoneal (i.p.) 10 mg/kg cisplatin administration induced renal injury in rats. Our results showed that 10 mg/kg/day quinacrine decreased the mortality rate of rats from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…These findings may indicate oxidative cisplatin-induced damage in renal tissue. Our outcomes were in line with other studies that demonstrated comparable cisplatin toxicity effects ( 22 ). According to the previous findings, oxidative stress is one of the most implicated pathways in the pathogenesis of cisplatin’s cytotoxic effects ( 20 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings may indicate oxidative cisplatin-induced damage in renal tissue. Our outcomes were in line with other studies that demonstrated comparable cisplatin toxicity effects ( 22 ). According to the previous findings, oxidative stress is one of the most implicated pathways in the pathogenesis of cisplatin’s cytotoxic effects ( 20 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our outcomes were in line with other studies that demonstrated comparable cisplatin toxicity effects ( 22 ). According to the previous findings, oxidative stress is one of the most implicated pathways in the pathogenesis of cisplatin’s cytotoxic effects ( 20 22 ). In this study, cisplatin-receiving groups with harmine efficiently reduced the MDA and TAC.…”
Section: Discussionsupporting
confidence: 92%